Cant figure out please help
cant figure out please help - 1

Answers

Answer 1
Answer: you just need to change the x to 2 ...

thus making the entire operation the answer is : 5 of 13 = 5/13
 

I hope I was helpfull
Answer 2
Answer: All we have to do as the other question is PLUG IN the given X!
f(x)= (3x^2-7)/(4x^2-3)
given x is 2

f(2)=(3(2)^2-7)/(4(2)^2-3)
 
     =(12-7)/(16-3)
     =(5)/(13)

Answer=(5)/(13)


Related Questions

2, 10, 50, 250, ...Write a recursive formula for
I need help with the equation k=c+273 solve for c
Using this equation 36 -:6x3+2²-(3+5) how does the answer equal 32
True or false. You can replace any letter in function notation with any number.
Estimate the product of 46 x 31 = ________. Select the equation that correctly represents how to round each factor. (2 points)50 x 30 = ________45 x 35 = ________50 x 35 = ________40 x 30 = ________

A problem states: "There are 7 more girls than boys in a class. There are 23 students in the class in all. How many girls are there in the class?"What are the unknowns in this problem?

Answers

There are 15 more girls than boys

If you shift the quadratic parent function f(x))=x^2right 12 units what is the equation o the new function

Answers

hmm

the question doesn't look clear

Find the coordinates of the vertices after the given transformation. Reflection across x=-2. W(-4,-4)

Answers

Answer:

To reflect a point across the vertical line x = -2, we can use the formula:

(x, y) → (2c - x, y)

where c is the x-coordinate of the line of reflection. In this case, c = -2. Let's apply this formula to the point W(-4, -4):

W' = (2(-2) - (-4), -4)

= (-4 + 4, -4)

= (0, -4)

Therefore, after the reflection across x = -2, the coordinates of W(-4, -4) become W'(0, -4).

Step-by-step explanation:

How many solutions does the equation 9(x – 3) = 9x – 27 have?

Answers

Answer:2

Step-by-step explanation:

Forty-two is what percent of 70? A.21%

B.60%

C.74%

D.167%

Answers

60% is the answer you are seeking. 

What is 12-2x6 + 2/2 ?

Answers

12-2*6 + (2)/(2)= \n 12-12+1 = 0 + 1 = 1